Thermal Performance of “Quincha” Constructive Technology in a Mountainous Region - Cuitiño Rosales, Maria Guadalupe (2018)
Increasingly, families are choosing to build their homes using earth-based technologies. This is the case in Tudunqueral Ecovilla (eco village) located in Uspallata Valley, Mendoza, Argentina. In this Andes Mountain Area, the houses primarily have been built with “Quincha” (also known as “wattle and daub”). Specifically, this paper aims to evaluate the thermal performance of the eco village’s Multi-Purpose Centre (MPC) which is a “Quincha” construction. Indoor temperature and relative humidity measurements and all external variables of climate (temperature, relative humidity, solar radiation and wind speed and direction) has been registered for winter and summer seasons. Thermography to evaluate local thermal situations of walls, ceilings and floors has been used. An interesting feature is that MPC has a Trombe Wall as passive solar system for heating it. Implementing energy conservation strategies coupled with the use of “quincha” as constructive technology allow for excellent results in the face of the rigorous climate of the mountain environment. It has proven that although low outdoor temperatures of -6°C were recorded, at the same time indoor temperatures was near 10°C, that means a temperature difference (in-out) of around 16°C. As well, while outdoor thermal amplitude reached 26°C, with the optimization of the MPC the thermal range indoors was 6.25°C. And the monetary cost for the optimization is US$3200 which is acceptable for the thermal benefits.